Direct regulation of shikimate, early phenylpropanoid, and stilbenoid pathways by Subgroup 2 R2R3‐MYBs in grapevine. (3rd March 2022) - Orduña, Luis; Li, Miaomiao; Navarro‐Payá, David; Zhang, Chen; Santiago, Antonio; Romero, Pablo; Ramšak, Živa; Magon, Gabriele; Höll, Janine; Merz, Patrick; Gruden, Kristina; Vannozzi, Alessandro; et al.
Significance Statement: Subgroup 2 R2R3 MYBs have been shown to upregulate stilbene synthase expression in grapevine; however, their broader roles in the regulation of secondary metabolism remained unclear. Combining whole genome gene co‐expression networks, cistrome data for MYB13/14/15, and MYB15 overexpression we identified new regulatory targets across stilbenoid, early phenylpropanoid and shikimate pathways. We demonstrate the validity of this approach via the biochemical characterization of new ROMT targets and provide the networks and cistrome data to the community. SUMMARY: The stilbenoid pathway is responsible for the production of resveratrol in grapevine ( Vitis vinifera L.). A few transcription factors (TFs) have been identified as regulators of this pathway but the extent of this control has not been deeply studied. Here we show how DNA affinity purification sequencing (DAP‐Seq) allows for the genome‐wide TF‐binding site interrogation in grape. We obtained 5190 and 4443 binding events assigned to 4041 and 3626 genes for MYB14 and MYB15, respectively (approximately 40% of peaks located within −10 kb of transcription start sites). DAP‐Seq of MYB14/MYB15 was combined with aggregate gene co‐expression networks (GCNs) built from more than 1400 transcriptomic datasets from leaves, fruits, and flowers to narrow down bound genes to a set of high confidence targets. The analysis of MYB14, MYB15, and MYB13, a third uncharacterized member of Subgroup 2 (S2), showed that in addition to the few previously known stilbene synthase ( STS ) targets, these regulators bind to 30 of 47 STS family genes. Moreover, all three MYBs bind to several PAL, C4H, and 4CL genes, in addition to shikimate pathway genes, the WRKY03 stilbenoid co‐regulator and resveratrol‐modifying gene candidates among which ROMT2‐3 were validated enzymatically. A high proportion of DAP‐Seq bound genes were induced in the activated transcriptomes of transient MYB15 ‐overexpressing grapevine leaves, validating our methodological approach for delimiting TF targets. Overall, Subgroup 2 R2R3‐MYBs appear to play a key role in binding and directly regulating several primary and secondary metabolic steps leading to an increased flux towards stilbenoid production. The integration of DAP‐Seq and reciprocal GCNs offers a rapid framework for gene function characterization using genome‐wide approaches in the context of non‐model plant species and stands up as a valid first approach for identifying gene regulatory networks of specialized metabolism.